Semiotic Analysis of Visual Illustration In The Animation “Legend of Garuda Wisnu Kencana” - Putra, Gede Lingga Ananta Kusuma; Yasa, Gede Pasek Putra Adnyana; Pramayasa, I Made Hendra Mahajaya (Sean Institute, 2024)
The animation